PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN PARIGI MOUTONG - Andri (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This study aims to determine the work environment and motivation on employee performance at the Department of Population and Civil Registry Parigi Gunung District. So the objectives to be achieved in this study are: 1) to find out whether the work environment influences employee performance at the Population and Civil Registration Office in Parigi Moutong Regency. 2) to find out whether motivation influences employee performance at the Population and Civil Registry Service in Parigi Moutong Regency. 3) to find out whether the work environment and motivation affect the performance of employees at the Population and Civil Registration Service in Parigi Moutong Regency. The results of this study indicate that: 1) the work environment influences the performance of employees at the Department of Population and Civil Registration of Parigi Moutong Regency. 2) Motivation affects the performance of employees at the Population and Civil Registry Office of Parigi Moutong Regency. 3) the work environment and motivation jointly affect the performance of employees at the Department of Population and Civil Registration of Parigi Moutong Regency.